The AI revolution and its literary reflections: A mixed-methods study of resistance and acceptance in contemporary English fiction from readers’ and authors’ perspectives - Fadlalla Ali, Elsadig Hussein; Usmani, Saima; Kousar, Mahmooda; Anwar, Riffat; Ali Alshamrani, Rawan Mesfer; Abdelmalik, Widad Ahmed Ibrahim (Research Journal in Advanced Humanities, 2026)
The blistering development of the field of artificial intelligence (AI) has already started to change the literary production, breaking the concept of authorship, originality, and creativity. This research examines the expression of resistance and acceptance of AI in modern English fiction by examining the textual expression and perceptions of the readers and the author. It incorporates both qualitative and quantitative research to analyze ten pieces of AI-related literature (2020-2025) and collect information on 200 readers and 20 authors/critics. Thematic analysis was used to analyze thematic innovation, narrative structure, and accounts of human-machine interaction as observed in texts by authors including Margaret Atwood, Kazuo Ishiguro, and Ian McEwan. The survey utilized a five-point Likert scale across five dimensions: creativity, authenticity, engagement, ethics, and innovation. Employed reliability testing, descriptive statistics, independent t-test, and Pearson correlation for quantitative evaluation. Results indicate the reliability test coefficient (Cronbach’s α = 0.87). Descriptive statistics found strong positive responses, with inventiveness receiving the highest average score (M = 4.12). The independent t-test showed significant differences between readers and authors in Creativity (t = 2.85, p = 0.005). Pearson correlation also showed a strong positive link between creativity and invention (r = 0.70, p < 0.01). AI supports new narrative styles such as non-linear and co-creative storytelling yet raises ethical and artistic concerns.